D PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ANDROID MENGGUNAKAN SOFTWARE ISPRING PADA MUATAN IPA KELAS V SEKOLAH DASAR - wirangga, ilham; Arsil; Risdalina (Jurnal Tunas Pendidikan, 2024)
This research aims to determine the procedures for developing media-based learningAndroid usesoftware ispring in the fifth grade science content in elementary schools, the sub-theme is how the body processes food, and to determine the suitability of media-based learningAndroid usesoftware ispring in class V science content, sub-theme how the body processes food in elementary school. The research method was carried out by researchers using a development model or in English it is calledResearch and Development (R&D). In this development research, the model used is the ADDIE development model. The research results show that the level of feasibility of learning media is based onAndroid usesoftware iSpring in the science content for class V Elementary School, the sub-theme is how the body processes food as a learning medium based on assessments: 1) Material Expert, 2) Language Expert, 3) Media Expert, 4) Teacher Assessment. Thus, learning media is basedAndroid usesoftware iSpringin the fifth grade science content in elementary school, the sub-theme is how the body processes food suitable for use.